2016
DOI: 10.1016/j.cotox.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic targets in Nrf2-dependent protection against neonatal respiratory distress disease predicted by cDNA microarray analysis and bioinformatics tools

Abstract: Hyperoxia exposure of newborn rodents has served as a model for bronchopulmonary dysplasia (BPD) phenotypes found in a sub-population of human premature infants. We previously demonstrated that Nrf2 modulates molecular events during saccular-to-alveolar lung maturation and also has a protective role in the pathogenesis of hyperoxia-induced acute lung injury, mortality, arrest of saccular-to-alveolar transition, and lung injury, using Nrf2-deficient and wild-type neonate mice. In this review, we describe how wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…AREs are found in many antioxidant genes and are responsible for upregulating cellular defenses (NRF2 pathway reviewed in [ 23 ]). Enhancement of the NRF2 activity has demonstrated protective effects in several models of lung injury [ 24 , 25 , 26 , 27 , 28 ]. As a result, modulation of NRF2 has become an attractive drug target for inflammatory diseases (reviewed in [ 27 ]).…”
Section: Discussionmentioning
confidence: 99%
“…AREs are found in many antioxidant genes and are responsible for upregulating cellular defenses (NRF2 pathway reviewed in [ 23 ]). Enhancement of the NRF2 activity has demonstrated protective effects in several models of lung injury [ 24 , 25 , 26 , 27 , 28 ]. As a result, modulation of NRF2 has become an attractive drug target for inflammatory diseases (reviewed in [ 27 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed it was previously documented that tobacco-induced emphysema was independent of NF-κB [32]. Reduction of PIR was detected in neonatal mouse respiratory distress disease by cDNA microarray analysis [33]. The plausible explanation is that COPD is a multifactorial and complex disease, involved in variety of factors and cells [15], the inhibition or inactivation of PIR in each stage of COPD need further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 deficiency in immature lung aggravated lung injury and alveolar arrest induced by hyperoxia in neonates. 21 Studies have shown that Nrf2 increased survival in hyperoxic conditions and attenuated hyperoxia-induced alveolar growth inhibition in newborn mice. 22 Therefore, as an antioxidant factor, Nrf2 has an important protective effect on oxidative stress induced by hyperoxia exposure in the respiratory tract.…”
Section: Group (N = 3) Nrf2 Mir-125bmentioning
confidence: 99%